Sosialisasi Peraturan Daerah No. 13 Tahun 2014 Dan No.14 Tahun 2014 - Paulus Kombo Allo Layuk (The Community Engagement Journal, 2018)
This community engagement activity is to provide socialization of regional regulation number 13 of 2014 and number 14 of 2014 at Merauke Regency. This regional regulation socialization is expected to enhance participants’ understanding of the substance of the two regulations on the principal of the management of local property so that each unit of regional apparatus is able to prepare financial statements and assets according to the regulation that has been established. The participants of this activity are around 95 people. Then, the result of this activity is the need for capacity building in understanding the regulations for the treasurer and PPTK.